Peran Pendidikan Kewirausahaan Dalam Meningkatkan Minat Mahasiswa Berwirausaha di Era Digital - Hamdan, Hamdan (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
Entrepreneurship education plays a vital role in fostering entrepreneurial spirit among students, particularly in the ever-evolving digital era. This research aims to analyze the role of entrepreneurship education in enhancing students' interest in entrepreneurship in the digital age. Using qualitative methods, literature analysis serves as the primary data source. Findings suggest entrepreneurship education boosts students' entrepreneurial interest, requiring continuous curriculum evaluation to align with technological advancements. Mentorship support and inclusive environments are crucial, along with strategies encompassing digital skills. Collaboration among institutions, industries, and governments ensures curriculum relevance. Continuous evaluation enhances entrepreneurship education effectiveness. Thus, developing market-relevant curricula, strengthening industry partnerships, and leveraging digital technology for engagement and accessibility are strategic steps to enhance entrepreneurship education's role in inspiring and preparing students for entrepreneurship in the digital era